The adjuvant G3 promotes a Th1 polarizing innate immune response in equine PBMC - Stina Hellman; Bernt Hjertner; Bror Morein; Caroline Fossum (Veterinary Research, 2018)
Abstract The immunomodulatory effect of a new particulate adjuvant, G3, alone or in combination with agonists to TLR2/1 or TLR5 was evaluated in cultures of equine PBMC. Exposure to the G3 adjuvant up-regulated genes encoding IFN-γ, IL-1β, IL-6, IL-8, IL-12p40 and IL-23p19 in the majority of the horses tested, indicating that the G3 adjuvant induced a pro-inflammatory and Th1 dominated profile. In accordance, genes encoding IL-13, IL-4, IL-10 and TGF-β remained unaffected and genes encoding IFN-α, IL-17A and TNF-α were only occasionally and weakly induced. The two TLR agonists Pam3CSK4 (TLR2/1) and FliC (TLR5) induced cytokine profiles characterized by a clear induction of IL-10 as well as up-regulation of the genes encoding IL-1β, IL-6 and IL-8. The presence of G3 modified this response, in particular by reducing the FliC and Pam3CSK4 induced production of IL-10. Furthermore, G3 acted in synergy with Pam3CSK4 in enhancing the production of IFN-γ whereas G3 combined with FliC increased the gene expression of IL-8. Thus, the G3 adjuvant seems to have the capacity to promote a Th1 polarizing innate immune response in eqPBMC, both by favouring IFN-γ production and by reducing production of IL-10 induced by co-delivered molecules. These features make G3 an interesting candidate to further evaluate for its potential as an adjuvant in equine vaccines.